From Exclusivity to Inclusivity: The Evolution of Palembang's Da'wah Movement and Its Contribution to National Development - Wiendyarti, Wiendyarti; Muchtar, Aflatun; Noupal, Muhammad (MUHARRIK: Jurnal Dakwah dan Sosial, 2024)
The emergence of various religious movements often negatively impacts the understanding of Islam, causing diverse reactions and unrest within the community due to the intensity of their propaganda and rapid growth. However, this phenomenon does not apply to the Indonesian Islamic Propagation Institute (LDII). This religious community organization has deep historical roots in Indonesia. Although it was banned in the past, it has persisted in its mission to remain active and disseminate its message. Over time, the dynamics and evolution within LDII have enabled it to establish a significant presence in contemporary society. This paper aims to explore the essence of LDII, including its origins, primary founders, and organizational development, particularly in the city of Palembang. Additionally, this paper seeks to examine the transformation of its propagation activities, where LDII not only employs conventional methods but also integrates technology and media. This study provides a comprehensive overview of LDII's historical background, the transitions it has undergone, and its current position in society. By examining these aspects, this paper endeavors to offer accurate and objective information about LDII's history and development, contributing to a better understanding of its role and influence within Indonesian society.